Non‐isotopic RNA In Situ Hybridization on Embryonic Sections. Issue 1 (5th January 2015) - Touahri, Yacine; Adnani, Lata; Mattar, Pierre; Markham, Kathryn; Klenin, Natalia; Schuurmans, Carol
Abstract: This unit describes methods for non‐isotopic RNA in situ hybridization on embryonic mouse sections. These methods can be used to follow the spatiotemporal dynamics of gene expression in an embryonic tissue of interest. They involve the use of labeled (e.g., digoxygenin, FITC) antisense riboprobes that hybridize to a specific mRNA in the target tissue. The probes are detected using an alkaline phosphatase−conjugated antibody recognizing the label and a chromogenic substrate. This method can be used to: (1) assess the expression of a single gene within a tissue, (2) compare the expression profiles of two genes within a tissue, or (3) compare the distribution of a transcript and protein within a tissue. While this approach is not quantitative, it provides a qualitative assessment of the precise cell types where a gene is expressed, which is not easily achievable with other more quantitative methods such as quantitative PCR. © 2015 by John Wiley & Sons, Inc.